Social capital and institutional quality: A cross-country analysis of economic output - Lee, Yvonne Lean Ee (2013)
Research on economic output has evolved in the quest to explain the output discrepancies between countries. This research proposes that current economic models can be enhanced by including social capital and institutions in the analysis of economic growth. This can minimise the ‘residual’ found in established economic growth models. In order to include social capital in an economic growth model, a comprehensive and practical definition of social capital is needed. To overcome the obstacle that there is no widely-accepted definition of social capital, this research used Durlauf (2004)’s perspective that definitions of social capital should comprise of the functional and causal perspectives as a jumping off point. The functional perspective of social capital is where social capital consists of a concept which defines a set of actions – trust, norms, networks and associations, and civic engagement, which are the basis of social capital measurement in this research.